Energy and sea power : challenge for the decade - Walsh, Don, 1931-; Cappellari, Marjorie; Pacific Coast Sea Power Forum (8th : 1980 : Monterey, Calif.) (New York : Pergamon Press)
Includes bibliographical references and index.